Support or subvert? Assessing devolution's effect on central power during Kenya's 2017 presidential rerun. Issue 2 (3rd April 2019) - Waddilove, Hannah
ABSTRACT: Devolution introduced new local-level political offices in order to transform Kenyan politics by reducing the high stakes around the presidential race. The controversy over the 2017 presidential election rerun, however, saw pressure on county-level politicians to support either the ruling party or opposition coalition, underlining the important intersection between national and county politics. Using a broadened definition of 'political linkages', this paper explores the logics shaping how and why county-level politicians responded to the rerun as they did, comparing ruling party and opposition areas. Different forms of linkage politics indicate that devolution's effect on central power is not uniform across counties, challenging the view that devolution simply leads to a recentralisation of power. The reproduction of national partisan divides at the county level suggests that devolution's effect on central power is contingent partly on the way that national and county political alliances intersect. Given Kenya's fluid national electoral alliances, devolution's effect on central power is therefore not stable and may change with each electoral cycle.